Biodegradation study of PDLA/cellulose microfibres biocomposites by Pseudomonas aeruginosa. Issue 5 (23rd February 2021) - Mbarki, Khadija; Fersi, Mariem; Louati, Ibtihel; Elleuch, Boubaker; Sayari, Adel
ABSTRACT: Aerobic biodegradation of biocomposites has been studied in both solid and liquid media. The research was concentrated on the biodegradation under aerobic and mesophilic conditions using poly-d -lactic acid (PDLA) and PDLA/cellulose microfibres (CMFs) samples as the sole carbon source. To determine the efficiency of the biodegradation, quantitative (mass variations, optical density (OD)) and qualitative (FTIR, NMR and SEM) analyses have been used to follow the polymer changes after degradation. The weight loss and OD of the biocomposites samples PDLA/CMFs were slower than that of pristine PDLA. The PDLA displayed the most important loss of weight (7.09%, 8.95%) compared to its initial weight and the lowest weight loss was detected in PDLA/CMF300 (1.04%, 2.19%) in solid and liquid mediums respectively. Also, the OD value of PDLA was increased from the seven days (0.381) to the last day (0.969). It appears that the major rate-determining factor affecting material degradation was its crystallinity without or with minimal assistance from abiotic factor because crystalline phases inhibit the diffusion of small water molecules. Otherwise, the Pseudomonas aeruginosa was isolated from Mediterranean soil has been found to be a novel candidate to biodegrade PDLA under mesophilic conditions. GRAPHICAL ABSTRACT: UF0001